Analiza pojęć „logika” i „logiczny” w encyklikach Jana Pawła II - Lapis, Włodzimierz (Investigationes Linguisticae, 2011)
In this paper I examine the perception of the concepts of ‘logic’ and ‘logical’ by John Paul II, The source material includes his 14 encyclicals (though both words occur only in eight of them a total of 38 times). As it turns out, the Pope sees logic as a science, a human system, or activity (human or divine). He uses the term ‘logical’ to refer to the ‘logical conclusion’ and ‘logical thinking’.